Comparison between balanced truncation and modal truncation techniques for linear state‐space symmetric systems. Issue 6 (1st April 2015) - Ha, Minh Binh; Chu, Minh Binh; Sreeram, Victor
Abstract : In this study, two well‐known model reduction techniques: balanced truncation and modal truncation are compared. The comparison is based on their error bound formulas for a special class of systems derived in this study. The comparison is illustrated by a numerical example.